Down syndrome and Alzheimer's disease: Common pathways, common goals. Issue 6 (12th December 2014) - Hartley, Dean; Blumenthal, Thomas; Carrillo, Maria; DiPaolo, Gilbert; Esralew, Lucille; Gardiner, Katheleen; Granholm, Ann-Charlotte; Iqbal, Khalid; Krams, Michael; Lemere, Cynthia; Lott, Ira; Mobley, William; et al.
Abstract: In the United States, estimates indicate there are between 250, 000 and 400, 000 individuals with Down syndrome (DS), and nearly all will develop Alzheimer's disease (AD) pathology starting in their 30s. With the current lifespan being 55 to 60 years, approximately 70% will develop dementia, and if their life expectancy continues to increase, the number of individuals developing AD will concomitantly increase. Pathogenic and mechanistic links between DS and Alzheimer's prompted the Alzheimer's Association to partner with the Linda Crnic Institute for Down Syndrome and the Global Down Syndrome Foundation at a workshop of AD and DS experts to discuss similarities and differences, challenges, and future directions for this field. The workshop articulated a set of research priorities: (1) target identification and drug development, (2) clinical and pathological staging, (3) cognitive assessment and clinical trials, and (4) partnerships and collaborations with the ultimate goal to deliver effective disease‐modifying treatments.